2019
DOI: 10.3390/f10060527
|View full text |Cite
|
Sign up to set email alerts
|

Tree Biomass Equations from Terrestrial LiDAR: A Case Study in Guyana

Abstract: Large uncertainties in tree and forest carbon estimates weaken national efforts to accurately estimate aboveground biomass (AGB) for their national monitoring, measurement, reporting and verification system. Allometric equations to estimate biomass have improved, but remain limited. They rely on destructive sampling; large trees are under-represented in the data used to create them; and they cannot always be applied to different regions. These factors lead to uncertainties and systematic errors in biomass esti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
40
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 56 publications
(65 citation statements)
references
References 52 publications
(128 reference statements)
4
40
0
3
Order By: Relevance
“…In this study, we showed that WD gradients were a large source of uncertainty in tree-level AGB estimations and that they propagated systematic errors (bias) across our datasets that were far from being negligible (c. 10%). As TLS technology will likely play an increasing role in the development of nondestructive AGB allometries 10,11,52 and the direct assessment of AGB at the stand level (notably for the calibration of upcoming satellite sensors 53 ), care should be taken not to let the gain in the precision of wood volume be offset by the use of biased WD estimates. Here, we followed and generalized a seminal study 39,41 in which the approach differed significantly from previous approaches 45,46 in proposing to collect WD samples at specific locations in trees that would presumably be representative of the mean tree WD.…”
Section: Characterizing Wd Vertical Profilesmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we showed that WD gradients were a large source of uncertainty in tree-level AGB estimations and that they propagated systematic errors (bias) across our datasets that were far from being negligible (c. 10%). As TLS technology will likely play an increasing role in the development of nondestructive AGB allometries 10,11,52 and the direct assessment of AGB at the stand level (notably for the calibration of upcoming satellite sensors 53 ), care should be taken not to let the gain in the precision of wood volume be offset by the use of biased WD estimates. Here, we followed and generalized a seminal study 39,41 in which the approach differed significantly from previous approaches 45,46 in proposing to collect WD samples at specific locations in trees that would presumably be representative of the mean tree WD.…”
Section: Characterizing Wd Vertical Profilesmentioning
confidence: 99%
“…This destructive method therefore offers limited promise for providing representative allometric equations for the estimated three trillion trees on Earth 9 . Terrestrial LiDAR scanning (TLS) has recently emerged as a nondestructive method not only for calibrating allometric biomass models 10,11 but also for performing measurements of volume, and by conversion biomass, at the stand level 9 . TLS is now being promoted by the Intergovernmental Panel on Climate Change (IPCC) in its Good Practice Guidelines (GPG) for national greenhouse gas inventories, as tropical countries aim to implement more efficient and precise methodologies 12 .…”
mentioning
confidence: 99%
“…These measurements include forest inventory (Liang et al, ) leaf angle distribution (Vicari, Pisek, & Disney, ), structural parameters (Trochta, Krůček, Vrška, & Král, ; Wang, Hollaus, Puttonen, & Pfeifer, ), above‐ground volume and biomass (AGB) (Calders et al, ; Gonzalez de Tanago et al, ; Momo Takoudjou et al, ). Moreover, allometric equations can be non‐destructively performed with data derived from TLS (Lau et al, ; Momo Takoudjou et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…(3) airborne [18] and terrestrial [19,20] LiDAR; and (4) forest reference emissions level (FREL) frameworks [21]. Chen et al [11] combine texture characteristics and backscatter coefficients of Sentinel-1 with multispectral information derived from Sentinel-2 and traditional field inventory data to develop above-ground biomass (AGB) prediction models using machine learning.…”
mentioning
confidence: 99%
“…The LiDAR studies in this Special Issue present work on a regional scale using airborne LiDAR [18], as well as tree-level assessment of LAI [19] and AGB [20] from terrestrial LiDAR. Often, LiDAR is not available over large continuous areas but can be essential for the calibration and validation (cal/val) of many forest map products that have been derived using coarser resolution satellite observations.…”
mentioning
confidence: 99%